Chest trauma morbidity and mortality by penetrating injury - Cabezas Barragán, Lincoln (Revista Universidad de Guayaquil, 2010)
Chest trauma is responsible for 25% of annual trauma deaths in Latin America and they could be closed, opened and by penetrating objects. Its treatment could be complex and changeble depending of trauma, severity of lesion and complication with colateral and mixed injuries. Goals of this study were: 1. To Identify most common thoracic trauma types registered in Hospital Luís Vernaza Emergency Service; 2. To identify most common emergency treatments; 3. To identify most common affected intrathoracic organs; 4. To determine trans and postsurgical mortality rate; 5. To register most frequent post surgery complications. Retroprospective, analytical and unidirectional methodology was applied. Penetrating gun trauma was the most common clinical injury, 81%. Left anterolateral thoracotomy was performed in 72%. Heart was the most affected organ followed by the left lung; trans surgical mortality is 2% and postoperative 20%, associated with abdominal visceral lesions. Main shock postoperative complications was 52% and respiratory distress syndrome 76%.
Keywords: Chest trauma; Penetrating injury mortality